THE ING NGARSA SUNG TULADHA COOPERATIVE LEARNING MODEL AND STUDENTS' PROBLEM SOLVING ABILITIES - Hutagaol, Kartini; Saija, Louise; Panjaitan, Maru M. J. (Universitas Pelita Harapan, 2020)
This paper describes one way that teachers as educators can face the challenges of the industrial revolution 4.0, namely by instilling and preparing creative and character-based leaders. Education as character building can be implemented using Ki Hajar Dewantara's leadership concepts, namely Ing Ngarsa Sung Tuladha, Ing Madya Mangun Karsa, and Tut Wuri Handayani. The concept of leadership was first adopted as a cooperative learning model which emphasized exemplariness in group learning. The group leader is called tuladha and is the facilitator of the group. Tuladha utilizes the Internet of Things. Before the teaching and learning process in class, information, concepts or ideas, and examples are posted by the teacher to the tuladha. This study is an experimental study with the sample used meeting the prerequisites of the statistical test used. The results showed that students' mathematical problem solving abilities increased significantly using the Ing Ngarsa Sung Tuladha cooperative learning model over the usual method. The category of improving students' mathematical problem solving abilities that obtain the Ing Ngarsa Sung Tuladha cooperative learning model is in the high category.